Optimization of Precoding Phase Distribution for Frequency-Multiplication Vector Signal Generation - Xinying Li (IEEE Photonics Journal, 2017)
Generation of optical vector millimeter-wave (mm-wave) signal based on Mach–Zehnder intensity modulator with frequency multiplication can reduce bandwidth requirement of optical and electrical components. A phase precoding scheme with constellation optimization is experimentally demonstrated in one 144-GHz mm-wave signal generation system with frequency sextupling. The bit-error-ratio (BER) performance at one BER of 3.8 × 10–3, hard-decision forward-error-correction threshold, is improved by over 3 dB using this novel scheme for 4-Gbaud quadrature-phase-shift-keying signal at D-band (110–170 GHz).